Strategi Transformasi Digital pada Perusahaan PT Lokabyte Digital Innovations Menggunakan Metode High Fidelity dan Prototype - Musantono, Agus Eko; Yulianto, Rachman; Saputra, Muhammad Riyo Nicholas; Ningsih, Pasya Wahyu Permata (Jurnal Informatika dan Komputer, 2025)
Digital transformation is an urgent need for companies to remain relevant and competitive in the digital era. This research aims to develop a prototype website design that supports PT Lokabyte Digital Innovations digital transformation strategy. Using high fidelity and prototyping methods, this research processes an interactive platform that is close to the final product, providing an opportunity for users to test functionality and usability in depth before full implementation. Data was collected through semi-structured interview and questionnaires with twenty respondents, who evaluated the visual appearance, navigation, interface consistency, and system efficiency. The test results showed that the usability result of 96%, success rate of 100% and time-based efficiency of 100% proved that the prototype design met the users’ needs, while constructive criticism was identified on the efficiency aspect of the system. These findings provide a foundation for PT Lokabyte Digital Innovations to develop a website that not only supports digital transformation, but also enhances the company’s competitiveness in the evolving market.